Evonik starts up production units for crosslinking activators; clarifies new group structure. Issue 2 (February 2015) - Unknown
Abstract : In Germany, Evonik has started up two new units for the production of crosslinking additives at its multi-user site in Wesseling. Triallyl cyanurate (TAC) and triallyl isocyanurate (TAICROS®) are described as 'high-quality crosslinking activators' for use in plastics and rubber. The new units are backwardly integrated with an existing plant at the site for the production of cyanuric chloride, one of the starting materials for both TAC and TAICROS.